PENGARUH LEVERAGE, DEBT MATURITY, KEBIJAKAN DIVIDEN, DAN CASH HOLDINGS TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar Di BEI tahun 2017) - Aditya Damarjati; Fuad Fuad (Diponegoro Journal of Accounting, 2018)
The aims of this research are to determine about (1) the effect of leverage on  firm’s financial performance, (2) the effect of debt maturity on firm’s financial performance, (3) the effect of devidend policy on firm’s financial performance, and (4) the effect of cash holdings on firm’s financial performance. The data of this research is taken from manufacturing industries on Indonesian Stock Exchange (BEI) 2017. This research uses purposive sampling method. With this method, 60 firms are considered as sampel. This research use multiple regresion analysis with Eviews 8.The results of this research are (1) leverage has no effect on firm’s financial performance, (2) debt maturity has significant positive effect on firm’s financial performance, (3) dividend policy has no effect on firm’s financial performance, and (4) cash holdings has no effect on firm’s financial performance.